Cybersecurity policy framework requirements for the establishment of highly interoperable and interconnected health data spaces - Luidold, Christian; Jungbauer, Christoph (Frontiers in Medicine, 2024)
This paper examines cybersecurity policy framework requirements for establishing highly interoperable and interconnected health data spaces, with a focus on the European Health Data Space (EHDS) and its corresponding joint action Towards European Health Data Space (TEHDAS). It explores the challenges of ensuring data security within an increasingly digital and collaborative healthcare environment, emphasizing the need for robust policy management to protect sensitive health information across diverse healthcare systems and supply chains. Through an analysis of use cases and held expert workshops, the study identifies key requirements for enhancing cybersecurity measures, fostering cross-border data exchange, and ensuring compliance with regulatory standards. It illustrates the practical implications of cybersecurity policies in a real-world scenario, demonstrating how they can be applied to enhance data security and policy effectiveness.